The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s1677-55382008000500013
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation of rabbit corpus cavernosum smooth muscle and aortic vascular endothelium induced by new nitric oxide donor substances of the nitrosyl-ruthenium complex

Abstract: Introduction: Endothelial dysfunction characterized by endogenous nitric oxide (NO) deficiency made 56% of patients affected with erectile dysfunction decline treatment with PDE-5 inhibitors. New forms of treatment are currently being developed for this group of patients. Materials and Methods:The study compared the effect of sodium nitroprusside (SNP) and two substances of the nitrosylruthenium complex, cis-[Ru(bpy)2(SO 3 )(NO)]PF-6-9 ("FONO1") and trans-[Ru(NH 3 )4(caffeine)(NO)]C13 ("LLNO1") on relaxation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…For instance, the up-regulation of phosphodiesterase type 5 (PDE-5) reduces the levels of cGMP in penile tissue, thus impair penile erection (Boswell-Smith et al 2006). In addition, the increased level of cGMP in penile tissues is dependent on NO-induced activation of guanyl cyclase, hence, maximum concentration of NO in the penile tissue is required (Cerqueira et al 2008). In the ED, the increased activity of arginase reduces production of NO, as arginase catalyzes the conversion of arginine to urea and ornithine, thereby reducing arginine levels that could be used for NO production by NO synthase (NOs).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the up-regulation of phosphodiesterase type 5 (PDE-5) reduces the levels of cGMP in penile tissue, thus impair penile erection (Boswell-Smith et al 2006). In addition, the increased level of cGMP in penile tissues is dependent on NO-induced activation of guanyl cyclase, hence, maximum concentration of NO in the penile tissue is required (Cerqueira et al 2008). In the ED, the increased activity of arginase reduces production of NO, as arginase catalyzes the conversion of arginine to urea and ornithine, thereby reducing arginine levels that could be used for NO production by NO synthase (NOs).…”
Section: Introductionmentioning
confidence: 99%
“…In the present experiment we attempted to acutely reverse the vasoconstrictor actions of systemic NO blockade with L-NAME by Rut-bpy (NO donor) in anesthetized rats. Studies have demonstrated that Rut-bpy induced maximum relaxation in rat aortic rings 6 , in vitro. In our study the use of Rut-bpy normalized MAP in hypotensive anesthetized rats but was not able to modify the MAP in rats with hypertension induced by L-Name.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been demonstrated that metal nitrosyl complexes may induce a decrease in blood pressure levels in hypertensive rats 5 . The novel metallopharmaceutical Rut-bpy (Cis-[Ru(bpy) 2 (SO 3 )(NO)]PF 6 ) is a potent vasodilator capable of releasing intracellular NO and activating guanylate cyclase 6 . Besides producing higher maximum relaxation in aortic rings than sodium nitroprusside at similar molar basis, Rut-bpy is associated with higher levels of NO release without being photosensitive or releasing cyanide 6,7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past years much attention has been given to nitrosyl-ruthenium complexes and their potential pharmacological use, especially due to their rapid NO release [15] as well as low level of toxicity [16][17][18]. Several ruthenium compounds have been synthesized and purified, but so far none has been tested in studies of experimental brain ischemia and reperfusion.…”
Section: Introductionmentioning
confidence: 99%